Nutrition in sports: present situation and prospects - Kuznetsova, M. A.; Klochkova, S. V.; Lavrinenko, S. V.; Nikityuk, D. B. (Theory and Practice of Physical Culture, 2018)
The study overviews the present situation with sport nutrition, specifies priority issues for discussion and analyzes progress opportunities in this area. Due nutrition is increasingly recognized as one of the key conditions for the athletes being healthy and successful in sports since the modern training systems claim growing energy costs. Sport researchers have developed efficient diets for different sports, with special foodstuffs of high biological value being increasingly applied in the high-calorific diets. The study offers an analytical overview of the available literature on the special foodstuffs and diets applicable in the sport systems and new developments in this field. The Federal Research Center for Nutrition, Biotechnology and Food Safety has developed and tested a new "NutriSport" multilevel test system to diagnose nutritional deficiencies and optimize the athletes` diets to improve their adaptation resource, sport form and competitive progress. The new test and diet system offers a variety of special individual diets for elite athletes customizable to their personal needs - rated and analyzed by the high-tech physicality, adaptability and nutritional status test methods. Benefits of the new system have been proved in practice and verified by the athletes` competitive progress in different events.